2014
DOI: 10.1039/c4cc00863d
|View full text |Cite
|
Sign up to set email alerts
|

Propargylamine–isothiocyanate reaction: efficient conjugation chemistry in aqueous media

Abstract: A coupling reaction between secondary propargyl amines and isothiocyanates in aqueous media is described. The reaction is high-yielding and affords cyclized products within 2-24 h. A functionalized ether lipid was synthesized in 8 steps, formulated as liposomes with POPC and conjugated to FITC under mild conditions using this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The fluorescein-thiazolidines 813 were obtained under mild conditions (20 °C, water and tert-butanol) with excellent yields (78–81%). The reaction progress was also monitored, and it was found that a mixture of thiourea and thiazolidine (2:3 ratio) intermediates were formed after 3 h, but after 24 h, only the thiazolidine products remained, implying a successive two-step reaction mechanism …”
Section: Reactivity Of Propargylaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescein-thiazolidines 813 were obtained under mild conditions (20 °C, water and tert-butanol) with excellent yields (78–81%). The reaction progress was also monitored, and it was found that a mixture of thiourea and thiazolidine (2:3 ratio) intermediates were formed after 3 h, but after 24 h, only the thiazolidine products remained, implying a successive two-step reaction mechanism …”
Section: Reactivity Of Propargylaminesmentioning
confidence: 99%
“…The reaction progress was also monitored, and it was found that a mixture of thiourea and thiazolidine (2:3 ratio) intermediates were formed after 3 h, but after 24 h, only the thiazolidine products remained, implying a successive two-step reaction mechanism. 435 Finally, Beauchemin and co-workers reported the syntheses of a series of substituted thiazolidines 816 using Nisothiocyanate precursors 814. Treatment of 814 with a base (Et 3 N) under microwave irradiation led to the formation of the isothiocyanate intermediate 815, which in turn reacts with propargylamines to afford thiazolidines 816 in good yields.…”
Section: Synthesis Of Thiazoles and Thiazolines From Propargylaminesmentioning
confidence: 99%
“…Seeking for a greener approach towards thiazolidines of type 30 , the group of Clausen has proposed a base-catalyzed protocol using t -BuOH in water at 20 °C for a quite efficient cyclization between secondary N -propargylamines 28 and fluorescein isothiocyanate 29 ( Scheme 7 ) [ 89 ].…”
Section: Reviewmentioning
confidence: 99%
“… 15 Coupling of oligoethylene glycol mesylates 5–9 with compound 1 with gave the corresponding BTA dimers 13–17 ( Scheme 2 ), and the final products were purified by HPLC. 16 …”
Section: Resultsmentioning
confidence: 99%